Sb Doped CuMnAs for Antiferromagnetic Spintronics - Barton, Luke (2023)
Enhancement of conventional electronic logic devices has been achieved with the consideration of electron spin, predominantly in ferromagnetic (FM) materials, for more than a decade. In computation and logic devices antiferromagnet (AF) materials have been a more recent hot topic after demonstrating the writing and reading of information with electrical current pulses on thin films of single crystal collinear AF CuMnAs. Desirable for their robust resistance to external fields, terahertz dynamics and lack of stray field, AFs have opened up new avenues for efficient spintronic devices.